Autonomous Surgical Robots and Their Future in Healthcare - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Autonomous Surgical Robots and Their Future in Healthcare The Scalpel of Tomorrow: Autonomous Surgical Robots and the Evolution of the Operating Room Th...
Keywords: Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning; Medical Ethics